Project Based Learning Model: Its Effect in Improving Students' Creative Thinking Skills - Anisa, Nur; Hijriyah, Umi; Diani, Rahma; Fujiani, Dwi; Velina, Yessy (Indonesian Journal of Science and Mathematics Education, 2023)
Creative thinking skills are one of the primary skills in 21st-century. The purpose of this research was to determine the PjBL Model's effect on students' creative thinking skills in physics. This research was a quasi-experimental research. The population of this research was all tenth-grade science students of SMA N 2 Bandar Lampung. The instrument in this study was test instrument to measure students' creative thinking skills. Based on the data, the PjBL model affected the creative thinking skills of students in physics materials evidenced by the results of data analysis with a sig value of 0.00, which was lower than 0.05. Therefore, H1 was accepted or there were differences in students’ creative thinking skills. Therefore, it can be concluded that the PjBL model affects students' creative thinking skills on physics material. It is recommended for further researchers to apply the PjBL model to other learning materials.